2019
DOI: 10.1246/cl.190391
|View full text |Cite
|
Sign up to set email alerts
|

Switching of Fluorescence Wavelength Caused by Phase Separation of Pyrene in Poly(N-isopropylacrylamide) Gel

Abstract: Pyrene (Py) contained in poly(N-isopropylacrylamide) gel (NIPA gel) that is swollen by water emits excimer-like derived fluorescence. However, as dehydration proceeded with increasing temperature, the luminescence changed to the monomer-derived one. Changes of it occurred continuously and reversibly around the lower critical solution temperature of NIPA gel. Because the gel interior becomes a hydrophobic environment in the shrunken state, the Py molecules can diffuse. However, it gathers like an oil droplet in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…We attributed this observation to the sudden dissolution of the preassociated pyrene into the (comparably more) hydrophobic polymer backbone, once a threshold d s was surpassed. This phenomenon was discovered recently and in parallel to our own work by Hamasaki and co-workers on pyrene solution-blended into poly­( N- isopropylacrylamide) hydrogels . However, in our materials, this effect was considerably more pronounced as the covalent attachment of the pyrene units to the polymer backbone allowed higher pyrene loading preventing its precipitation from aqueous solution at high d s .…”
Section: Hydrogels From Pyrene Macro-cross-linkerssupporting
confidence: 72%
See 1 more Smart Citation
“…We attributed this observation to the sudden dissolution of the preassociated pyrene into the (comparably more) hydrophobic polymer backbone, once a threshold d s was surpassed. This phenomenon was discovered recently and in parallel to our own work by Hamasaki and co-workers on pyrene solution-blended into poly­( N- isopropylacrylamide) hydrogels . However, in our materials, this effect was considerably more pronounced as the covalent attachment of the pyrene units to the polymer backbone allowed higher pyrene loading preventing its precipitation from aqueous solution at high d s .…”
Section: Hydrogels From Pyrene Macro-cross-linkerssupporting
confidence: 72%
“…This phenomenon was discovered recently and in parallel to our own work by Hamasaki and co-workers on pyrene solution-blended into poly( N- isopropylacrylamide) hydrogels. 38 However, in our materials, this effect was considerably more pronounced as the covalent attachment of the pyrene units to the polymer backbone allowed higher pyrene loading preventing its precipitation from aqueous solution at high d s . Aggregation-caused quenching (ACQ) as origin for these observations 39 was ruled out due to the increase of the monomer emission accompanying the decrease of the excimer emission ( Figure S27 ).…”
Section: Hydrogels From Pyrene Macro-cross-linkersmentioning
confidence: 71%
“…Li and co‐workers developed a method of visualizing and detecting protein coacervates with an aggregation‐induced emission fluorogen [27] . Pyrene (py) is a hydrophobic and fluorescent molecule due to the four conjugated benzene rings [28] . Wong and co‐workers introduced a light‐switching dipyrene probe to detect phase‐separated biomolecules taking advantage of the difference in fluorescent intensities of the monomers in hydrophobic environments of the coacervates and excimers in aqueous solutions [25] .…”
Section: Introductionmentioning
confidence: 99%
“…35−38 We recently reported that if water was introduced to a PNIPA gel with trapped pyrene, pyrene excimers formed even if the concentration of trapped pyrene was low. 39 Because hydrophobic pyrene molecules have low solubility in water, the pyrene and water were thought to separate in the gel. We found that the pyrene actually formed an excimer in the swollen gel.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Because of the carboxyl groups and amino groups, poly- N -isopropylacrylamide (PNIPA) can become hydrated at low temperatures and swell as it absorbs water. However, PNIPA gel has a lower critical solution temperature (LCST) of approximately 306.5 K, which means that it hydrates and dehydrates rapidly. We recently reported that if water was introduced to a PNIPA gel with trapped pyrene, pyrene excimers formed even if the concentration of trapped pyrene was low . Because hydrophobic pyrene molecules have low solubility in water, the pyrene and water were thought to separate in the gel.…”
Section: Introductionmentioning
confidence: 99%